Protective effect of Arque-Ajeeb on acute experimental diarrhoea in rats - Ahmad Ghufran; Qasmi Iqbal; Khan Naeem; Khan Mohd; Zafar Shadab (BMC, 2004)
Abstract Background Diarrhoea is a major health problem for children worldwide, accounting for 5-8 million deaths each year. Arque-Ajeeb (AA) is a compound formulation of Unani medicine. It is reputed for its beneficial effects in the treatment of diarrhoea and cholera, but the claim of its efficacy is yet to be tested. Therefore the present study has been planned to investigate the real efficacy of this drug in rats. Methods The effect of Arque-Ajeeb was investigated for antidiarrhoeal activity against charcoal-induced gut transit, serotonin-induced diarrhoea and PGE2-induced small intestine enteropooling in rats. The control, standard and test groups of experimental animals were administered with normal saline (p.o.), diphenoxylate hydrochloride (5 mg/kg, p.o.) and Arque-Ajeeb (0.07 ml and 0.14 ml/kg, p.o.) respectively except the control group of PGE2-induced small intestine enteropooling which received only 5% ethanol in normal saline (i.p.). Charcoal (10 ml/kg, p.o.) and serotonin (600 μg/kg, i.p.) were administered after 30 min, while PGE2 (100 μg/kg, p.o.) was administered immediately afterwards. The distance traveled by charcoal in small intestine was measured after 15 and 30 min of charcoal administration, diarrhoea was observed every 30-min for six hour after serotonin administration and the volume of intestinal fluid was measured after 30 min of PGE2 administration. Results Arque-Ajeeb (0.07 ml and 0.14 ml/kg) significantly inhibited the frequency of defaecation and decreased the propulsion of charcoal meal through the gastrointestinal tract, reduced the wetness of faecal droppings in serotonin-induced diarrhoea and also reduced the PGE2-induced small intestine enteropooling. Conclusion Arque-Ajeeb may have potential to reduce the diarrhoea in rats. Thus the drug may prove to be an alternate remedy in diarrhoea.